Social pediatrics: weaving horizontal and vertical threads through pediatric residency. Issue 1 (December 2017) - van den Heuvel, Meta; Martimianakis, Maria; Levy, Rebecca; Atkinson, Adelle; Ford-Jones, Elizabeth; Shouldice, Michelle
Abstract Background Social pediatrics teaches pediatric residents how to understand disease within their patients' social, environmental and political contexts. It's an essential component of pediatric residency training; however there is very little literature that addresses how such a broad-ranging topic can be taught effectively. The aim of this study was to determine and characterize social pediatric education in our pediatric residency training in order to identify strengths and gaps. Methods A social pediatrics curriculum map was developed, attending to 3 different dimensions: (1) the intended curriculum as prescribed by the Objectives of Training for Pediatrics of the Royal College of Physicians and Surgeons of Canada (RCPSC), (2) the formal curriculum defined by rotation-specific learning objectives, and (3) the informal/hidden curriculum as reflected in resident and teacher experiences and perceptions. Results Forty-one social pediatric learning objectives were extracted from the RCPSC Objectives of Training for Pediatrics, most were listed in the Medical Expert (51%) and Health Advocate competencies (24%). Almost all RCPSC social pediatric learning objectives were identified in more than one rotation and/or seminar. Adolescent Medicine (29.2%), Pediatric Ambulatory Medicine (26.2%) and Developmental Pediatrics (25%) listed the highest proportion of social pediatric learning objectives. Four (10%) RCPSC social pediatric objectives were not explicitly named within learning objectives of the formal curriculum. The informal curriculum revealed that both teachers and residents viewed social pediatrics as integral to all clinical encounters. Perceived barriers to teaching and learning of social pediatrics included time constraints, particularly in a tertiary care environment, and the value of social pediatrics relative to medical expert knowledge. Conclusions Despite the lack of an explicit thematic presentation of social pediatric learning objectives by the Royal College and residency training program, social pediatric topics are integrated, taught and learned throughout the entire curriculum. Special attention needs to be given to the hidden curriculum and system barriers that may impede social pediatric education.